KETOgenic diet therapy in patients with HEPatocellular adenoma: study protocol of a matched interventional cohort study. Issue 2 (15th February 2022) - Oudmaijer, Christiaan Albert Johan; Berk, Kirsten Anna; van der Louw, Elisabeth Johanna Theresia Maria; de Man, Rob; van der Lelij, Aart-Jan; Hoeijmakers, Jan Hendrik Jozef; IJzermans, Jan
Abstract : Introduction: Hepatocellular adenoma (HCA) is an uncommon, solid and benign liver lesion, mainly occurring in women using oral contraceptives. Patients are advised to stop using oral contraceptives (OC) and, as overweight is frequently observed, dietary restrictions. Metabolic changes are assumed to play a role and it has been suggested that diet may help to reduce tumour size. A low-calorie ketogenic diet (LCKD) has been shown to induce weight loss and multiple metabolic changes, including the reduction of portal insulin concentrations, which downregulates hepatic growth hormone receptors. Weight reduction and an LCKD can potentially reduce the size of HCAs. Methods and analysis: We designed a matched, interventional cohort study to determine the effect of an LCKD on the regression of HCA. The study population consists of female subjects with an HCA, 18–50 years of age, body mass index>25 kg/m 2, who are entering a surveillance period including cessation of OC. A historical control group will be matched. The intervention consists of an LCKD (approximately 35 g carbohydrate/1500 kcal/day) for 3 months, followed by a less strict LCKD for 3 months (approximately 60 g carbohydrate/1500 kcal/day). Main study endpoint is the diameter of the HCA after 6 months, as compared with the historic control group. Secondary endpoints include adherence, quality of life, change in physical activity, liver fat content, body weight, body composition and resting energy expenditure. Ethics and dissemination: The medical ethical committee has approved the study protocol, patient information files and consent procedure and other study-related documents and procedures. Trial registration number: NL75014.078.20; Pre-results. https://www.trialregister.nl/trial/9092